2015
DOI: 10.1021/jacs.5b04040
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Tuning of Li-Ion Diffusion in Layered Li(NixMnyCoz)O2

Abstract: Using ab initio calculations combined with experiments, we clarified how the kinetics of Li-ion diffusion can be tuned in LiNixMnyCozO2 (NMC, x + y + z = 1) materials. It is found that Li-ions tend to choose oxygen dumbbell hopping (ODH) at the early stage of charging (delithiation), and tetrahedral site hopping (TSH) begins to dominate when more than 1/3 Li-ions are extracted. In both ODH and TSH, the Li-ions surrounded by nickel (especially with low valence state) are more likely to diffuse with low activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
170
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 324 publications
(187 citation statements)
references
References 27 publications
17
170
0
Order By: Relevance
“…41-44 and 45; original research on the material can be found in Ref. [50][51][52][53][54][55][56][57][58][59][60]. In this work, we apply our thermodynamic modeling to Ni 0.6 Mn 0.2 Co 0.2 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…41-44 and 45; original research on the material can be found in Ref. [50][51][52][53][54][55][56][57][58][59][60]. In this work, we apply our thermodynamic modeling to Ni 0.6 Mn 0.2 Co 0.2 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, it suffers from the disadvantage of high cost and poor safety. Recently, some derivative layered cathodes are explored that are safer and more affordable, such as LiNi x Mn y Co z O 2 (x + y + z = 1) systems [9][10][11][12]. These materials are expanding in their application.…”
Section: Introductionmentioning
confidence: 99%
“…78 Near the fully lithiated limit, Li diffusion occurs primarily via an ODH pathway. 77 To understand the effect of Al-doping on Li diffusion, we investigate the Li hopping mechanism from one Li octahedral site to another vacant Li octahedral site, via an ODH pathway. To compute the Li diffusion profile we created a single Li vacancy (i.e.…”
mentioning
confidence: 99%